Acoustic Characterization of Composites Made of Gypsum and Pineapple Leaf Fibres (American Journal of IR 4.0 and Beyond, 2023)
The research sought to characterize the acoustic properties of gypsum composite which contained 2% pineapple leaf fibre (PALF) and plain gypsum with different thicknesses. The impact of composite thickness and 2%PALF inclusion on the acoustic properties of the PALF-gypsum composite (sound absorption coefficient and sound transmission loss) were examined. A comparison of the sound transmission loss and sound absorption coefficient for frequencies between 60 and 1600 Hz was made possible by acoustic tests using an impedance tube. The sound absorption results showed that adding 2 percent PALF to gypsum significantly improves acoustic properties when compared to plain gypsum. When comparing composite samples 2% PALF (C2) to control samples (C0), the noise reduction coefficient (NRC) result revealed a 50% increase. The composite materials containing 2% PALF had the highest NRC value of 0.18. Furthermore, due to the increase in composite thickness, the sound transmission loss of 2% PALF resulted in greater acoustic insulation in the range of 30 dB. The findings of the experiments show that PALF can greatly increase the insulating qualities of gypsum composites.